A Phase IIa Controlled Human Malaria Infection and Immunogenicity Study of RTS, S/AS01E and RTS, S/AS01B Delayed Fractional Dose Regimens in Malaria-Naive Adults. (20th July 2020) - Moon, James E; Ockenhouse, Christian; Regules, Jason A; Vekemans, Johan; Lee, Cynthia; Chuang, Ilin; Traskine, Magali; Jongert, Erik; Ivinson, Karen; Morelle, Danielle; Komisar, Jack L; Lievens, Marc; et al.
Abstract: Background: A previous RTS, S/AS01B vaccine challenge trial demonstrated that a 3-dose (0-1-7–month) regimen with a fractional third dose can produce high vaccine efficacy (VE) in adults challenged 3 weeks after vaccination. This study explored the VE of different delayed fractional dose regimens of adult and pediatric RTS, S/AS01 formulations. Methods: A total of 130 participants were randomized into 5 groups. Four groups received 3 doses of RTS, S/AS01B or RTS, S/AS01E on a 0-1-7–month schedule, with the final 1 or 2 doses being fractional (one-fifth dose volume). One group received 1 full (month 0) and 1 fractional (month 7) dose of RTS, S/AS01E . Immunized and unvaccinated control participants underwent Plasmodium falciparum –infected mosquito challenge (controlled human malaria infection) 3 months after immunization, a timing chosen to potentially discriminate VEs between groups. Results: The VE of 3-dose formulations ranged from 55% (95% confidence interval, 27%–72%) to 76% (48%–89%). Groups administered equivalent formulations of RTS, S/AS01E and RTS, S/AS01B demonstrated comparable VE. The 2-dose group demonstrated lower VE (29% [95% confidence interval, 6%–46%]). All regimens were well tolerated and immunogenic, with trends toward higher anti-circumsporozoite antibody titers in participants protected against infection. Conclusions: RTS, S/AS01E can provide VE comparable to an equivalent RTS, S/AS01B regimen in adults, suggesting a universal formulation may be considered. Results also suggest that the 2-dose regimen is inferior to the 3-dose regimens evaluated. Clinical Trial Registration: NCT03162614 Abstract : We explored the ability of different delayed fractional dose-regimens of RTS, S/AS01-formulations to increase vaccine efficacy using CHMI. The pediatric RTS, S/AS01E-formulation was comparably efficacious with an equivalent RTS, S/AS01B regimen in adults. The two-dose regimen evaluated was inferior to the three-dose regimens.